Peers or parents? On non-monetary incentives in schools - Valentin Wagner; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper presents the result of a field experiment on the effectiveness of non-monetary incentives on pupils' achievement on a mathematical multiple choice test. Our sample consists of 2113 pupils of deprived and high-achieving secondary schools in Germany. Based on a pre-study, we compare the effectiveness of (i) a medal (ii) a letter of praise to the parents and (iii) a delegation of choice over incentives. The effect of non-monetary incentives depends on pupils' socio-economic background. While they constitute a potentially cost-effective and easily implementable method of motivation in Non-High Schools, predetermined non-monetary incentives crowd out intrinsic motivation for pupils in High Schools. In contrast, the endogenous choice of the reward increases pupils' willingness to prepare for the test and mitigates the negative effect of predetermined external rewards in High Schools. Additionally, in the delegation treatment, we find that low-achieving pupils typically choose a reward with a higher signaling value to their parents, independent of the school type.
Keywords: C93; I20; I21; J1; 330; non-monetary incentives; field experiment; education; incentive choice; effort; socio-economic background